Moisture Conditions in Exterior Wooden Walls and Timber During Production and Use - Olsson, Lars (2014)
Thermal insulation of building envelopes has improved over the years. This means that building envelope have become more susceptible to defects, with an increased risk of moisture damage. The criteria for energy consumption have become more rigorous, but the shift should not lead to moisture problems. New knowledge about timber and wooden constructions is required in order to better meet these criteria. The purpose of this thesis has been to examine moisture levels in timber and external wooden walls during the construction and usage phases, as well as provide recommendations for good moisture safety.The work is based on seven publications, listed in chronological order from the construction process, and covers timber stacks at sawmills, factory production of wall elements and roof trusses, transportation to the building site, assembly, as well as follow-up of finished houses and structures in the usage stage. Mainly three methods, field test, calculation and laboratory test, have been used for evaluation of moisture levels, temperature and mould growth. The overall conclusion is that dry wooden structures and timber is required, which means that several minor adjustments need to be made to the construction practices, construction methods, products, materials, designs and structures currently being used, in order to achieve good moisture safety. In southern Sweden, there is a significant risk for mould growth on wooden studs in well-insulated north-facing external walls that lack external thermal insulation outside the wooden studs. In northern Sweden this risk is significantly lower or there is no risk at all. A small amount of rain that does not create running or dripping water on timber materials and which can dry out the same day should not lead to a risk of mould growth. In general, however, precipitation and material exposed to rain pose a high risk of mould growth. There is a risk of mould growth on timber surfaces that are exposed to an outdoor air in southern Sweden for more than a month, but not at all ...